Serum level of proteins involved in apoptosis and autophagy in patients with type 2 diabetes and non-alcoholic fatty liver disease - Ya. A. Krasner; V. V. Romanov; O. N. Fazullina; M. F. Osipenko; V. V. Klimontov (Сибирский научный медицинский журнал, 2024)
Aim of the study was to estimate the blood serum level of microtubule-associated protein 1 light chain 3 alpha (MAP1LC3alpha), beclin-1 (BECN-1), Bcl-2 (BCL-2), caspase-3 (CASP3) and autophagy related 5 (ATG-5) protein as potential markers of liver fibrosis in type 2 diabetes (T2D) patients with non-alcoholic fatty liver disease (NAFLD).Material and methods. A single center cross-sectional observational study was performed. Seventy four patients with T2D and NAFLD were included, 23 men and 51 women, aged 18 to 74 years. Transient elastography was used for the assessment of liver fibrosis. The severity of fibrosis was estimated using the Metavir sсore. In addition, indirect liver fibrosis indices APRI and FIB-4 were calculated. Serum concentration of MAP1LC3alpha, BECN-1, BCL-2, CASP and ATG-5 was measured by ELISA. We applied ROC analysis to assess the value of studied indicators in diagnosis of liver fibrosis.Results. Liver fibrosis stage F1 was verified in 16 subjects, stage F2 in 12, stage F3 in 7, and stage F4 in 19 individuals. Patients with advanced liver fibrosis (stage 3-4) when compared to those without fibrosis (stage 0–2) had higher content of MAP1LC3alpha (p = 0.01) and BECN-1 (p = 0.01). There were no significant differences in the level of BCL-2, CASP3 and ATG-5 between patients with different severity of fibrosis. In the ROC analysis, MAP1LC3alpha and BECN-1 showed significance for the diagnosis of severe liver fibrosis, which, however, did not exceed that of the APRI index.Conclusions. In patients with T2D and NAFLD, serum levels of MAP1LC3alpha and BECN-1 are associated with severe liver fibrosis.